Profiles of Emotional Intelligence and Their Relationship with Motivational and Well-being Factors in Physical Education - Méndez-Giménez, Antonio; Cecchini, José Antonio; García Romero, Cristina (Madrid : Colegio Oficial de Psicólogos de Madrid, 2020)
Research on emotional intelligence (EI) and its relationship with motivational and health factors in educational contexts is scarce. The objectives of this study were three: (a) to explore emotional intelligence profiles of adolescents; (b) to examine how these profiles relate to different types of motivation, basic psychological needs, friendship goals, subjective well- being, and intentions to be physically active; and (c) to analyze how these emotional profiles evolve during a full year in physical education contexts. It is a longitudinal study with three measurement occasions. Participants were 282 students (151 boys and 131 girls) from six high schools (Mage = 13.03, SD = 0.93). Hierarchical and k-means cluster analysis were performed, three inter-group MANOVAs (one for each time) and one 2 x 3 (group x time) MANOVA to explore longitudinal changes. Two EI clusters emerged: high EI (n = 168) and low EI (n = 114). Significant effects were found for the group in the three MANOVAs. The high EI cluster was more adaptive, self-determined, with greater psychosocial adjustment, subjective well-being, and intentions to be physically active.
En inglés; resúmenes en español e inglés.
Descripción basada en metadatos suministrados por el editor y otras fuentes.
Descripción basada en Psicología educativa: revista de los psicólogos de la educación, vol. 26, n. 1 (enero 2020), P. 27-36.
Recurso electrónico. Santa Fe, Arg.: elibro, 2024. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a elibro.
Keywords: Análisis de clústeres.; Bienestar; Inteligencia emocional; Metas sociales; Motivación.; Salud; Artículos electrónicos.